A new genus and species of parasitic isopod (Bopyroidea: Entoniscidae) infesting pinnotherid crabs (Brachyura: Pinnotheridae) on the Atlantic coast of the USA, with notes on the life cycle of entoniscids. Issue 1 (16th December 2019) - McDermott, John J; Williams, Jason D; Boyko, Christopher B
Abstract: Pinnixion sexdecennia n. gen., n. sp. is described from three pinnotherid hosts: Austinixa gorei (Manning & Felder, 1989), Pinnixa chaetopterana Stimpson, 1860, and Zaops ostreus (Say, 1817). Females of the new species are distinguished from all other entoniscids by possessing two transverse lobes on oostegite 1 and fused oostegites 2–5; males have a pair of lateral expansions on each of the first two pleomeres. The epicaridium larvae of the new species also have a unique elongated, cylindrical terminal process on the pereopod 6 dactylus. Pinnixion sexdecennia n. gen., n. sp. exhibited highest prevalence (> 40%) in North Carolina and Florida. Examination of live specimens of P. chaetopterana infested with mature female isopods showed that larvae are liberated via a pore produced in the wall of the host's branchial chamber. Mature females of P. sexdecennia n. gen., n. sp. occupied nearly all available space within the host crab's hemocoel. Female P. chaetopterana had higher prevalence than males, and intensities of infestations were also greater in females. Evidence from all locations showed that mature parasites do not inhibit breeding or molting in the host. Our report is one of the few studies on the ecology and biology of entoniscids, a cryptic but ecologically important group of parasitic isopods. We also resolve long-standing nomenclatural issues involving Entione Kossmann, 1881 and Entioninae Codreanu, Codreanu & Pike, 1960, the subfamily to which the new genus and species belongs, by synonymizing Grapsion Giard & Bonnier, 1886 with Entione .